Mental Health Counseling: Thoughts on Defining a Professional Intervention field - Garita Pulido, Ana Victoria (Revista Electrónica Educare, 2013)
The purpose of this paper is to provide some thoughts on a series of points of view that will help us in defining mental health as an intervention field of counseling. Reference is made to the epistemological positioning adopted to understand health, which is focused on a contextual perspective. A health promotion model is proposed to support the counseling activity. The reasons for limiting the intervention to mental health promotion, which are related to theoretical and methodological references inherent to the discipline, are also explained. Recommendations are made on the aspects to be considered for both individual and collective approaches and for extending the professional practice of counselors with an efficient performance as mental health promoters.